Impact of Calving Dynamics on Kangilernata Sermia, Greenland. Issue 20 (14th October 2020) - Kane, Emily; Rignot, Eric; Mouginot, Jeremie; Millan, Romain; Li, Xin; Scheuchl, Bernd; Fahnestock, Mark
Abstract: Iceberg calving is a major component of glacier mass ablation that is not well understood due to a lack of detailed temporal and spatial observations. Here, we measure glacier speed and surface elevation at 3 min intervals using a portable radar interferometer at Kangilernata Sermia, West Greenland, for a period of 2 weeks in July 2016. We detect a 20% diurnal variation in glacier speed in phase with tidal height propagating kilometers inland. We find no speedup from ice shedding off the calving face or the detachment of floating ice blocks but a 30% speedup within a few hundred meters of the ice front that persists for days when calving removes full‐thickness grounded ice blocks. Within one ice thickness from the calving front, we detect maximum strain rates 2 to 3 times larger than observable from satellite data, which has implications for studying iceberg calving as a fracturing process. Plain Language Summary: The calving of icebergs from glaciers is a major process of mass loss along the margins of the Greenland Ice Sheet that is poorly understood because it is not well observed with existing systems. We present detailed field observations of glacier speed and elevation acquired every 3 min over 2 weeks along the calving front of a major glacier in Greenland to learn about these processes. We find that the glacier responds to changes in oceanic tide, namely, the glacier speeds up in phase with the tidal height of the ocean waters, and that only calving events that remove full‐thickness ice blocks that were resting on the ground, instead of being afloat, affect the glacier speed. Following the calving of grounded ice, the glacier speed is affected for several days but only within a few hundred meters of the ice front. Furthermore, we find that the glacier deformation regime near the ice front is more pronounced than observable from existing spaceborne radars, which has implications for the study of ice fracture, iceberg calving mechanisms, and modeling glacier dynamics. Key Points: Iceberg calving triggers glacier speedup in the proximity of the ice front when a full‐thickness grounded part of the glacier is removed Oceanic tides modulate Kangilernata glacier speed daily by 20% at least several km inland Maximum strain rates along the calving front are 2–3 times larger than previously thought